Relative timing of mitochondrial endosymbiosis and the “pre‐mitochondrial symbioses” hypothesis - Toni Gabaldón (2018)
Abstract The origin of eukaryotes stands as a major open question in biology. Central to this question is the nature and timing of the origin of the mitochondrion, an ubiquitous eukaryotic organelle originated by the endosymbiosis of an alphaproteobacterial ancestor. Different hypotheses disagree, among other aspects, on whether mitochondria were acquired early or late during eukaryogenesis. Similarly, the nature and complexity of the receiving host is debated, with models ranging from a simple prokaryotic host to an already complex proto‐eukaryote. Here, I will discuss recent findings from phylogenomics analyses of extant genomes that are shedding light into the evolutionary origins of the eukaryotic ancestor, and which suggest a later acquisition of alpha‐proteobacterial derived proteins as compared to those with different bacterial ancestries. I argue that simple eukaryogenesis models that assume a binary symbiosis between an archaeon host and an alpha‐proteobacterial proto‐mitochondrion cannot explain the complex chimeric nature that is inferred for the eukaryotic ancestor. To reconcile existing hypotheses with the new data, I propose the “pre‐mitochondrial symbioses” hypothesis that provides a framework for eukaryogenesis scenarios involving alternative symbiotic interactions that predate the acquisition of mitochondria. © 2018 The Authors. IUBMB Life published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology, 70(12):1188–1196, 2018